Colon capsule endoscopy: What we know and what we would like to know - Spada, Cristiano (World J Gastroenterol, 2014)
Colonoscopy is usually perceived as an invasive and potentially painful procedure, being also affected by a small, but definite, risk of major complications (cardiopulmonary complications, perforation, hemorrhage) and even mortality. To improve both acceptability and safety, PillCam Colon Capsule Endoscopy (CCE) (Given Imaging Ltd, Yoqneam, Israel) has been developed. CCE represents a non-invasive technique that is able to explore the colon without sedation and air insufflation. The Second Generation of Colon Capsule Endoscopy (PillCam Colon 2) (CCE-2) was proven to be an accurate tool to detect colonic neoplastic lesions when used in average risk individuals. To date, the evidence supports the use of CCE-2 in case of colonoscopy failure, in patients unwilling to perform colonoscopy and when colonoscopy is contraindicated. Other potential applications, such as colorectal cancer screening or diagnostic surveillance of inflammatory bowel disease need to be clarified. In this paper, the current “state of the art”, potential application of CCE and future needs are evaluated.